Genetic variabiity and character association for quality traits in recombinant inbred lines derived from inter sub-specific crosses of rice (Oryza sativa L.) (Bangladesh Journal of Botany, 2014)
The investigation was carried out to study the genetic parameters for quality and nutritional characters in 60 recombinant inbred lines (RILs) of rice. Analysis of variance revealed significant differences for all the traits. It was observed that grain yield per plant was positively significant associated with seed width, milling per cent, gelatinization temperature, amylose content and kernel breadth before cooking. Kernel length after cooking, seed width, milling per cent, amylose content and gelatinization temperature had positive direct effect on grain yield. Comprehensive examination of result revealed that the recombinant inbred lines tested for high yield in rice viz., RIL-77, 08, 99, 75, 10 and 13 were identified as superior. DOI: http://dx.doi.org/10.3329/bjb.v43i1.19756 Bangladesh J. Bot. 43(1): 97-99, 2014 (June)